2013
DOI: 10.4103/2045-8932.113184
|View full text |Cite
|
Sign up to set email alerts
|

Provider Recognition and Response to Echocardiographic Findings Indicating Pulmonary Hypertension in the Veterans Affairs Medical Center Population

Abstract: PH occurs alone or in association with many disorders. Many patients with transthoracic echocardiography (TTE) findings suggesting PH never receive additional evaluation. Patient characteristics and echocardiographic data associated with increased recognition of PH have not been fully evaluated. We evaluated TTE reports at the Cincinnati Veterans Affairs Medical Center from 2005 to 2006 retrospectively for findings highly indicative of PH: Estimated systolic pulmonary artery pressure (sPAP) ≥40 mmHg, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a prior study of veterans with abnormally high PAPs on echocardiogram, only a small fraction (5/227, 2.2%) ultimately underwent RHC. 5 In another study of veterans with a pulmonary artery systolic pressure ≥ 60 mmHg on echocardiogram, only a minority underwent further diagnostic testing such as pulmonary function testing with diffusion capacity measurement, V/Q scan or chest computed tomography angiography, or RHC. 4 Referral to a multidisciplinary PH clinic resulted in completion of guideline-recommended assessments 8 in the majority of our patients with PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prior study of veterans with abnormally high PAPs on echocardiogram, only a small fraction (5/227, 2.2%) ultimately underwent RHC. 5 In another study of veterans with a pulmonary artery systolic pressure ≥ 60 mmHg on echocardiogram, only a minority underwent further diagnostic testing such as pulmonary function testing with diffusion capacity measurement, V/Q scan or chest computed tomography angiography, or RHC. 4 Referral to a multidisciplinary PH clinic resulted in completion of guideline-recommended assessments 8 in the majority of our patients with PH.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite evidence of PH being a frequent finding on echocardiograms, studies have shown that PH is often mis- or underdiagnosed in both veterans 4 , 5 and non-veterans. 6 To address this issue at our VA medical center, we undertook efforts to establish a referral clinic for veterans with known or suspected PH.…”
mentioning
confidence: 99%
“…[13][14][15][16][17] However, although PH has major implications on morbidity and mortality, recent studies suggest that it is frequently overlooked and underrecognized. 18,19 Early diagnosis and treatment improve outcomes. Since RV function determines functional status, exercise capacity, and outcomes in PH, and since RV dysfunction is commonly observed in PH patients, we hypothesized that a substantial portion of patients with persistent dyspnea, despite negative CTPA for PE, have unrecognized RV dysfunction or overload on echocardiography that contributes to persistent symptoms and CTPA recidivism.…”
mentioning
confidence: 99%